PENERAPAN GOOD MANUFACTURING PRACTICES DAN WORK IMPROVEMENT IN SMALL ENTERPRISES PADA PEMBUATAN OPAK DI UMKM DESI - Abdul Azis Syarif; Uun Novalia Harahap; Yetti Meuthia Hasibuan; Adi Prasatya; Rahmat Wahyu (Jurnal Simetri Rekayasa, 2022)
Opak Desi UKM is an UKM engaged in producing opaque crackers made from sweet potatoes/cassava. However, the work environment in these SMEs still does not have a clean kitchen standard. This clean kitchen standard is known as the GMP rules (Good Manufacturing Practice). GMP is a guideline for how to produce food with the aim that producers meet the predetermined requirements to produce quality food products in accordance with consumer demands. The problem is that the production area in SMEs is less hygienic and uncomfortable for workers and the flow of materials that occur experience cross movement, which means they intersect and also occur double tracking which causes the production process to be hampered. This research was completed using the assessment of the GMP checklist to evaluate the overall work system. The results of the checklist assessment are processed using the AHP method. The results of the assessment show that the criteria for storage and material handling with a weight of 1.65658 for UKM Opak are work system improvement priorities. Some of the proposed recommendations for improving the work system are the design of the SSOP work system, GMP, and the design of a new layout adapted to food safety and hygiene standards. The recommendations are expected to be able to increase productivity in the production process as well as safer, healthier and more comfortable working conditions.